Microbiological Analysis of Poultry Feeds Along with the Demonstration of the Antibiotic Susceptibility of the Isolates and the Antibacterial Activity of the Feeds - Roy, Chanda Rani; Ahmed, Tasnia; Uddin, Md Aftab (Bangladesh Journal of Microbiology, 2019)
Poultry farms and poultry product processing industries are increasing worldwide to fill up the expanding demand for protein of the escalating population. To get good growth and more eggs from the domestic birds in the poultry farms, nutritious food supplements are commonly known as the poultry feed provided. These feeds also serve as sources of bacterial, fungal and viral contamination which in turn can cause diseases in the birds and ultimately can infect the consumers if the poultry is not processed and cooked properly. In this study, in order to determine the pathogenic bacterial load five different poultry feed samples sold in local markets of Dhaka city were analyzed. All samples harbored total viable bacteria up to 5.0×106 cfu/gm and total fungal count up to 4.5×105 cfu/gm. While Escherichia coli was absent in all samples; Klebsiella spp. and Aeromonas spp. were found to be present in only one sample (1.4×106 cfu/gm in sample 4 and 2.9×105 cfu/gm in sample 5 respectively). Staphylococcus aureus and Shigella spp. were found to be predominat in all the samples. Pseudomonas spp. and Vibrio spp. were present in 3 and 4 samples, respectively. Aeromonas spp., Vibrio spp., Salmonella spp. and Staphylococcus aureus showed 100% drug resistance towards ER, NA, NVB, KAN antibiotics. The finding of the study emphasis on the prevention of contamination through a sound maintenance of quality during poultry feeds preparation, storage and maintenance. Diseased birds and their excreta must be destroyed during poultry farming. Usage of excess antibiotics must be regulated as suggested from the data of the current study that shows high resistance of the bacterial isolates from the food. Finally, the consumers should process and cook the poultry items properly to save themselves from further food hazards. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 103-107